A coupled model of composite synthesis in combustion regime. Issue 1 (2nd January 2022) - Knyazeva, Anna Georgievna; Bukrina, Natalia Valerievna
Abstract : The work proposes a model for synthesising a 'metallic matrix–reinforcing inclusions' composite in a simplified reaction scheme. A suggested mathematical model takes into account the interdependence of thermal, chemical and mechanical phenomena. The problem includes kinetic equations for determining the composition of the synthesis products. The reactions are initiated by a thermal impulse from a surface. It was established that after some mathematical transformations and partial analytical solution, the model includes equivalent parameters of the reactions and equivalent thermophysical properties that depend on the mechanical modules. The model allowed us to study two variants of composite synthesis: in the quasi-stationary mode for a sample whose dimensions exceed the size of the heating and reaction zones, and in the unsteady mode for a finite-sized sample. It is shown that the consideration of the coupling of thermal, chemical and mechanical processes changes all the characteristics of conversion propagation and the values of stresses and strains in the reaction zone. The stresses in the reaction zone and in the products are affected by the parameters characterising the reaction itself. It is shown that there is a range of parameters at which a stable combustion wave is not formed.